2015
DOI: 10.1080/01916122.2015.1022908
|View full text |Cite
|
Sign up to set email alerts
|

Pollen morphology inAthenaeaSendtn. andAurelianaSendtn. (Solanaceae)

Abstract: Aureliana and Athenaea (Withaniinae, Solanaceae) are two genera of shrubs or small trees with centres of diversity in the Brazilian Atlantic Rain Forest. They are difficult to distinguish using gross morphology, and are traditionally segregated based on differences in fruiting calyx size. Pollen grains of all taxa were acetolysed, treated and examined with light and scanning electron microscopy, with the aim of identifying diagnostic characters. Microphotographs and illustrations of pollen grains are presented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Some other worker also reported the Pollen size range for W. somnifera , namely, Hussain () reported the size range 24 (26) 28 μm for W. somnifera, Al‐Quran () quoted the size range 25–29 × 29–33 μm for W. somnifera, and Perveen and Qaiser () also reported the size range 21.56 (25.81) 28.72 × 21.54 (28.8) 28.72 μm for W. somnifera type. Martins da Costa Rodrigues, Fernandes Falcão, Stehmann, and Girardi Bauermann () studied pollen morphology in Athenaea Sendtn and Aureliana Sendtn (Withaniinae, Solanaceae), the analysis showed that the pollen grains of both genera are very similar, differing in size‐related characters and also reported monad pollen grains with varying morphology, small to medium‐sized, lalongate endoapertures and long to extremely long colpi. Song, Gu, and Liu () also reported pollen morphology of selected species from the family Solanaceae from China and results suggested that the exine ornamentation of pollen grains could be divided into 11 types, made up of three types (cerebroid, granulate‐perforate‐punctate, and rugulate‐perforate).…”
Section: Discussionmentioning
confidence: 99%
“…Some other worker also reported the Pollen size range for W. somnifera , namely, Hussain () reported the size range 24 (26) 28 μm for W. somnifera, Al‐Quran () quoted the size range 25–29 × 29–33 μm for W. somnifera, and Perveen and Qaiser () also reported the size range 21.56 (25.81) 28.72 × 21.54 (28.8) 28.72 μm for W. somnifera type. Martins da Costa Rodrigues, Fernandes Falcão, Stehmann, and Girardi Bauermann () studied pollen morphology in Athenaea Sendtn and Aureliana Sendtn (Withaniinae, Solanaceae), the analysis showed that the pollen grains of both genera are very similar, differing in size‐related characters and also reported monad pollen grains with varying morphology, small to medium‐sized, lalongate endoapertures and long to extremely long colpi. Song, Gu, and Liu () also reported pollen morphology of selected species from the family Solanaceae from China and results suggested that the exine ornamentation of pollen grains could be divided into 11 types, made up of three types (cerebroid, granulate‐perforate‐punctate, and rugulate‐perforate).…”
Section: Discussionmentioning
confidence: 99%
“…(2015) thus recognized Athenaea as a synonym of Aureliana, and five new combinations were made, transferring all Athenaea species to Aureliana. Flower, fruit and pollen morphology corroborate the circumscription of these taxa as a single genus (Zamberlan & al., 2015;Rodrigues & al., 2016).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Both are exclusively Neotropical and have centers of diversity in southeastern Brazil (Barboza & Hunziker, 1989;Hunziker & Barboza, 1991;Hunziker, 2001). Phylogenetic studies based on DNA sequence data (Zamberlan & al., 2015) and morphological analysis of the calyx and pollen (Rodrigues & al., 2016) have shown the two genera are not distinct, and all taxa previously recognized as Athenaea were given new combinations in Aureliana. Zamberlan & al.…”
Section: ■ Introductionmentioning
confidence: 99%